Science of Cyber Security: Second International Conference, SciSec 2019, Nanjing, China, August 9-11, 2019, Revised Selected Papers - Liu, Feng; Xu, Jia; Xu, Shouhuai; Yung, Moti (Lecture Notes in Computer Science (11933), 2019)
This book constitutes the proceedings of the Second International Conference on Science of Cyber Security, SciSec 2019, held in Nanjing, China, in August 2019.The 20 full papers and 8 short papers presented in this volume were carefully reviewed and selected from 62 submissions. These papers cover the following subjects: Artificial Intelligence for Cybersecurity, Machine Learning for Cybersecurity, and Mechanisms for Solving Actual Cybersecurity Problems (e.g., Blockchain, Attack and Defense; Encryptions with Cybersecurity Applications).